Sir Harold Ridley and his fight for sight : he changed the world so that we may better see it - Apple, David J (SLACK, 2006)
The publication focuses on the career and life of Sir Harold Ridley, an ophthalmologist. Intended for professional and general public.
Keywords: Spojené království; dějiny 20. století; Ophthalmologists; Ophthalmology; oftalmologie; dějiny lékařství; History, 20th Century; oftalmologové; United Kingdom